Bridging to orthotopic heart transplant: Reducing the risk of intra-operative blood loss - Phoebe Miller, MS MD; Andrew Akcelik, MD; Alyssa Murillo, MD; Alison Baskin, MD; Alexander Merriman, PhD; Mohammad Arammash, BS; Shreyas Kiran, BS; Jason Smith, MD; Amy G. Fiedler, MD (JHLT Open)
Background: Orthotopic heart transplantation remains the gold standard for patients with end-stage heart failure. Many devices exist to bridge patients with heart failure to transplant. Impella 5.5 (Abiomed, Danvers MA) is an example of a temporary mechanical assist device, which prioritizes patients as Status 2 by the 2018 UNOS policy change, increasing their likelihood of transplantation. Given the increase in device use, we sought to compare intra-operative complications, particularly blood loss, between bridging strategies to transplantation. Methods: We conducted a single-institution retrospective analysis between January 2019 and May 2023. Results: A transfusion requirement was defined as greater than 4 units of blood given intra- or immediately post-operatively (24%, 22/93). The transfusion group was more likely to have had a prior sternotomy (82% vs. 48% p<0.01) and to be on a durable left ventricular assist device (LVAD) (45% vs. 21% p=0.02). There was no difference in anticoagulation or antiplatelet use prior to the odds ratio (OR). The use of Impella 5.5 did not increase the risk of intra-operative bleeding (14% vs. 21% p=0.44). In the adjusted outcomes, factors associated with intra-operative bleeding included average temperature and LVAD (OR 3.63 95% CI [1. −12.3], p=0.04) Conclusion: The shift to prioritize bridging devices has not been met with an increased risk of blood transfusion. We found that parameters such as a prior sternotomy, duration of temporary mechanical assist device (tMCS) use, and the presence of an LVAD were associated. This represents the first study to compare intra- and immediately post-operative transfusion data between bridging devices in the setting of transplantation.